Pengaruh Audit Internal dan Religiusitas Terhadap Kecurangan Pelaporan Keuangan - Lu'lu' Nafiati; Rintan Nuzul Ainy (Jurnal Bisnis dan Kewirausahaan, 2022)
Financial reporting fraud is the least common type of fraud, but causes the most significant median loss of USD 800,000. Given the magnitude of the impact of fraudulent financial reporting, academics need to understand the actions that can be used to reduce fraudulent financial reporting. This study aims to examine the effect of internal audit and religiosity on fraudulent financial reporting behaviour. Using an experimental study design, subjects were randomly assigned to two internal audit conditions (strong and weak) and their level of religiosity was measured (low and high). The results showed that a strong internal audit could mitigate fraudulent financial reporting behaviour. On the other hand, high religiosity does not affect fraudulent financial reporting behaviour. This paper differs from previous studies that examined fraudulent at the behavioural stage and no longer at the intention stage. This study also contributes to providing solutions to reduce fraudulent financial reporting behavior by using a combination of external factors (strong internal audit) and individual internal factors (religiosity).